Area-linguistic aspects of the language situation in the South-Bohemian borderland after the forced transfer of the German population = Arealnolingwistyczne aspekty sytuacji językowej w regionie południowoczeskim po osadnictwie populacji niemieckiej - Jaklová, Alena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This study deals with the changes in the language situation in the South-Bohemian borderland after WW II from the point of view of area linguistics, exploring the causes of linguistic changes from the perspective of social science, particularly historiography and political geography. South Bohemia is represented in the study by the regions of Prachatice and Vimperk: areas where, until the 1940s, the Germans outnumbered the Czech population.
Keywords: Area linguistics; South-Bohemian borderland; Czechs and Germans; German surnames; linguistic analysis of the underlying motivation of surnames; lingwistyka arealna; pogranicze południowoczeskie; Czesi; Niemcy; nazwiska niemieckie; lingwistyczna analiza ukrytej motywacji nazwisk